Here's the question you clicked on:
casidy_albright_96
Solve the following system using substitution: y=-4x-2 y=x+3
substitute y for x+3 solve for x final solution should be x= -1
could you show me how you got that?
Sure Like I said your going to substitute y for x+3 so your going to rewrite you problem as.. x+3=-4x-2 The next thing you need to do is get rid of one of the x's so your going to subtract x from both sides so your new equation is.. 3=-5x-2 (Because its understood that x=1) Your next step is to add 2 to both sides.. 5=-5x Now we want to get x by itself so we divide -5 on both sides, Giving you your final answer of -1=x
thank you so much!!!! :)